Tie Strength Dispersion and Alliance Portfolio Performance: The Moderating Effects of CEOs' Political and International Experience. (15th April 2021) - Bi, Jingyu; Xie, En; Sheng, Shibin
Abstract: Many firms simultaneously develop multiple alliances with different partners and face the challenges of managing a complex alliance portfolio that contains both strong and weak ties. How does this dispersion of tie strength affect alliance portfolio performance? This study examines the effect of tie strength dispersion on alliance portfolio performance, as well as the contingent effects of CEOs' experience. The empirical analyses, using a dataset consisting of 748 funds initiated by 62 fund management firms over a 10‐year period (2002–2011), reveal an inverted U‐shaped relationship between tie strength dispersion and alliance portfolio performance. The analyses also reveal that CEOs' political experience weakens, while their international experience strengthens, this inverted U‐shaped relationship.